Identification of novel allosteric inhibitors of mutant isocitrate dehydrogenase 1 by cross docking-based virtual screening - Zou, Fangxia; Pusch, Stefan; Deimling, Andreas von (Bioorganic & medicinal chemistry letters, 2018)
IDH1 mutation (mIDH1) occurs in 20-30% of gliomas and is a promising target for the cancer therapy. In this article, a cross docking-based virtual screening was employed to identify seven small molecules for the allosteric site of mIDH1. Compounds ZX01, ZX05 and ZX06 exhibited the potent inhibitory activity and the high selectivity against WT-IDH1, providing a good starting point for the further development of highly selective mIDH1 inhibitors. Importantly, the parallel artificial membrane permeation assay of the blood-brain barrier (PAMPA-BBB) identified ZX06 with a good ability to penetrate BBB. These findings indicate that ZX06 deserves further optimization as a lead compound for the treatment of patients with IDH1 mutated brain cancers.
Available online 13 December 2017
Gesehen am 24.06.2020